2019
DOI: 10.5897/jtehs2018.0424
|View full text |Cite
|
Sign up to set email alerts
|

Determination of polycyclic aromatic hydrocarbons in blood plasma of neurology patients

Abstract: The etiology of many neurological cases cannot be easily delineated, making the investigation, and treatment to be challenging. This study aims to screen the blood of neurology patients presenting for the first time in the hospital for Polycyclic Aromatic Hydrocarbons (PAHs) using Flame Ionization Detector -Gas Chromatography. Fourteen PAHs were detected in the samples. The results showed that flourene and phenanthrene were common to all the patients in the range (1.37 to 8.08 and 1.66 to 8.34 ng/mL respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Furthermore, Pleil et al summarized pyrene concentrations in blood and plasma from different studies, showing variation in the range of 3 pg/ml to 11 ng/ml (whole blood). But pyrene concentrations may range from 3 to 237 ng/ml in plasma of Nigerian neurology patients 63 . As plasma roughly constitutes 55% of the total blood volume, this corresponds to blood concentrations in the range of 1.65–130 ng/ml.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Pleil et al summarized pyrene concentrations in blood and plasma from different studies, showing variation in the range of 3 pg/ml to 11 ng/ml (whole blood). But pyrene concentrations may range from 3 to 237 ng/ml in plasma of Nigerian neurology patients 63 . As plasma roughly constitutes 55% of the total blood volume, this corresponds to blood concentrations in the range of 1.65–130 ng/ml.…”
Section: Discussionmentioning
confidence: 99%
“…But pyrene concentrations may range from 3 to 237 ng/ml in plasma of Nigerian neurology patients. 63 As plasma roughly constitutes 55% of the total blood volume, this corresponds to blood concentrations in the range of 1.65–130 ng/ml. Thus, the lowest exposure concentrations of the present study (5 μg/ml W150°C = 0.175 μg/ml pyrene) could be in the range of high, but realistic, real‐life blood concentrations in humans.…”
Section: Discussionmentioning
confidence: 99%
“…20 At the same time, it was observed that the CC genotypes had low levels of BPDE-DNA adduct levels this is supports findings of 21 Matullo et al, who stated that the carriers of CC showed a relatively lower levels of bulky DNA adduct in lymphocytes, which may be association with reduced capacity of DNA repair system. Also in meta-analysis conducted by Kiyohara et al 22 TT genotype of the XRCC1 rs 25487 (Arg399Gln) polymorphism found that was increased PAHs levels and it may be association with low DNA repair capacity. The results obtained in this study were agreement with other previous study stating that CT and TT genotype is represent a risk of various types of cancer like lung cancer caused by the environment.…”
Section: Effect Of Rs25487 Genotypes On B[a]p Levelsmentioning
confidence: 96%
“…In the study conducted at an outpatient neurology clinic, it was found that ranges of pyrene, fluoranthene, and acenaphthene concentrations in the blood plasma of the patients were between 2.96 and 236.86 ng/mL, 1.96 and 11.55 ng/mL, and 1.08 and 1.81 ng/mL, respectively. 91 In another study conducted at an Abattoir in Abuja, Nigeria, chronic occupational exposure of butchers to PAHs-containing fumes produced from burning tires used in de-furring of slaughtered animals was found to affect their lung health. 92 In the study the butchers presented with a forced expiratory volume, forced vital capacity ratio (FEV/FVC) of < 80% which according to the Global Initiative for Chronic Obstructive Disease is an indication of primary lung impairment.…”
Section: Health Effects Of Pah Contamination In Ssamentioning
confidence: 99%